1997
DOI: 10.1111/j.1365-2249.1997.236-ce1111.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective depletion of rectal lamina propria rather than lymphoid aggregate CD4 lymphocytes in HIV infection

Abstract: SUMMARYThe goal of this study was to examine the changes in lymphocyte populations in rectal mucosa during HIV infection and to study their relationship to mucosal immunity and to systemic depletion of CD4 lymphocytes. Rectal biopsies from 58 HIV-infected subjects and eight controls were studied. Frozen rectal tissue sections were stained with antibodies to CD4, CD3, CD8, and markers for macrophages. HIV-infected subjects were divided into early stage (no opportunistic infections) and AIDS groups. There was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 12 publications
0
71
0
Order By: Relevance
“…26 Later studies, also using immunohistochemistry, confirmed that that the GI tract was indeed significantly depleted of CD4 T cells. 27,31,32 Moreover, these observations were made in both the large and small intestine, indicating that the depletion of GI CD4 T cells involves the entire bowel. However, these studies were somewhat restricted in that the majority of the HIV-infected individuals studied were chronically infected with HIV or in the late stage of AIDS.…”
Section: Gastrointestinal Cd4 T-cell Depletionmentioning
confidence: 84%
“…26 Later studies, also using immunohistochemistry, confirmed that that the GI tract was indeed significantly depleted of CD4 T cells. 27,31,32 Moreover, these observations were made in both the large and small intestine, indicating that the depletion of GI CD4 T cells involves the entire bowel. However, these studies were somewhat restricted in that the majority of the HIV-infected individuals studied were chronically infected with HIV or in the late stage of AIDS.…”
Section: Gastrointestinal Cd4 T-cell Depletionmentioning
confidence: 84%
“…Impaired GC formation, structure, and function in the systemic compartment are well described in HIV-1-infected patients (59, 65, 66) and may also relate to changes in the isotype distribution of mucosal B cells during HIV-1 infection. Prominent data from HIV-1-infected humans and SIV-infected macaques suggest that widespread depletion of CD4 ϩ T cells in the effector lamina propria occurs early after infection, while these cells remain more numerous in mucosal inductive sites (12,39,67). Although these GC T cells could supply the signaling that B cells require to initiate CSR (see below), several studies have also shown that these cells can harbor HIV-1 or SIV (36,39,68).…”
Section: Discussionmentioning
confidence: 99%
“…Underlying these high rates may be the impaired Ab responses to luminal Ags, which complicate HIV-1 infection (5-10). The mechanisms of this impairment of B cell function may derive from T cell (11,12) or intrinsic B cell defects (13)(14)(15)(16). HIV-1 has been proposed to induce intrinsic defects in B cells through selective depletion of cells expressing Ig H chains of the third variable region family (V H 3) (17)(18)(19)(20)(21), which comprise about half of the expressed circulating V H repertoire (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Recent studies have highlighted the importance of early depletion of CD4 + T cells in the gut occurring after infection of humans with HIV-1 [1][2][3][4][5][6] and rhesus macaques with SIV [7][8][9][10][11]. These authors have observed a rapid and large reduction in the fraction of CD4 + T cells in the lamina propria (LP) of the gut, and several follow-up papers argued that this ''first cut'' is important for disease progression [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%